Елементи управління конкурентоспроможністю телекомунікаційних комапній - Franchuk, Olena; Petrova, Mariana; Tolkachova, Galina (Dr. Viktor Koval, 2018)
Introduction. The importance of telecommunications in the socio-economic sphere is growing, providing support for the development of the national economy, since the priority development of telecommunications, compared with the overall pace of economic development, significantly increases the competitiveness of the Ukrainian economy. Therefore, the management of telecommunications companies is defined as one of the priority areas of government in the face of growing competition, which makes the problem of increasing the competitiveness of telecommunications services and the telecommunications operator as a whole urgent. Aim and tasks. The aim of the article is to study the methodological issues of substantiating the elements of enterprise competitiveness in the telecommunications services market, as well as studying the gradation of the level of competitiveness and recommendations for their use in managing the competitiveness of an enterprise. Results. The scientific and theoretical approaches to the essence of the concept of «competitiveness» are considered. The study made it possible to form its own scientific vision of the economic category “competitiveness of telecommunication companies”. It is noted that modern global trends in the development of the telecommunications market affect its new type in the conditions of the formation of the information society. The main forms of competition in the telecommunications services market are considered. The features of modern telecommunications are highlighted. Disclosed policy in the space of competition regulation in the market of telecommunication services. Conclusions. Identified and analyzed the basics of managing the competitiveness of telecommunications companies operating in a competitive environment, which is characterized by constant technological innovation.. The main elements of the process of managing the competitiveness of telecommunications companies are substantiated as components of the internal and external environment that determine or can determine the future performance of the company in the international and domestic markets, which will help create the conditions for the implementation of a highly developed information and telecommunications infrastructure to provide telecommunications services to all segments of the population.